2022
DOI: 10.3390/s22239386
|View full text |Cite
|
Sign up to set email alerts
|

A Denoising Method for Mining Cable PD Signal Based on Genetic Algorithm Optimization of VMD and Wavelet Threshold

Abstract: When the pulse current method is used for partial discharge (PD) monitoring of mining cables, the detected PD signals are seriously disturbed by the field noise, which are easily submerged in the noise and cannot be extracted. In order to realize the effective separation of the PD signal and the interference signal of the mining cable and improve the signal-to-noise ratio of the PD signal, a denoising method for the PD signal of the mining cable based on genetic algorithm optimization of variational mode decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A denoising method that is based on WT and hard thresholding to eliminate remaining noise from the obtained PD signals was presented by Han et al [62]. Wang et al [63] suggested a denoising method based on wavelet threshold and VMD optimization with a genetic algorithm (GA) for mining cable PD signals. Additionally, thorough comparative analysis has been published in [64,65] to evaluate the effectiveness of WT, SVD, and VMD, the three denoising approaches, for acoustic signals produced by PD sources.…”
Section: Wavelet Transform-based Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…A denoising method that is based on WT and hard thresholding to eliminate remaining noise from the obtained PD signals was presented by Han et al [62]. Wang et al [63] suggested a denoising method based on wavelet threshold and VMD optimization with a genetic algorithm (GA) for mining cable PD signals. Additionally, thorough comparative analysis has been published in [64,65] to evaluate the effectiveness of WT, SVD, and VMD, the three denoising approaches, for acoustic signals produced by PD sources.…”
Section: Wavelet Transform-based Feature Extractionmentioning
confidence: 99%
“…It is an iterative process, ending inheritance after a specified number of generations. The algorithm involves six steps: encoding, initial population generation, fitness value evaluation, selection, crossover, and mutation [63]. This feature selection method, the GA, is part of the wrapper approach [117].…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…Considering this, noise rejection tools must operate in two steps. The first step should be focused on rejecting the non-pulsating noise signals by means of band stop or wavelet filters [ 2 , 15 , 16 , 17 , 18 , 19 , 20 ] and the second step should address rejecting pulsating noises by means of clustering tools [ 21 , 22 , 23 ]. The metrological tests are focused on analysing the error caused by the filtering tools when non-pulsating noise signals are rejected.…”
Section: Reference Pd Pulse Trains and Noise Signalsmentioning
confidence: 99%
“…To appropriately detect PD activity and perform accurate diagnosis, various measuring applications based on electromagnetic methods have been and continue to be developed [ 8 , 9 , 10 , 11 , 12 ]. These applications usually have specific functionalities, such as background noise filters to improve the sensitivity and PD source discrimination, as well as location and defect identification tools [ 3 , 4 , 13 , 14 ]. They also have the capacity to generate assisted or automatic alarms when a critical defect is identified [ 15 ].…”
Section: Introductionmentioning
confidence: 99%